Association of Cell Adhesion Molecules Contactin-6 and Latrophilin-1 Regulates Neuronal Apoptosis - Zuko, Amila; Oguro-Ando, Asami; Post, Harm; Taggenbrock, Renske L. R. E.; van Dijk, Roland E.; Altelaar, A. F. Maarten; Heck, Albert J. R.; Petrenko, Alexander G.; van der Zwaag, Bert; Shimoda, Yasushi; Pasterkamp, R. Jeroen; Burbach, J. Peter H. (Frontiers in Molecular Neuroscience, 2016)
In view of important neurobiological functions of the cell adhesion molecule contactin-6 (Cntn6) that have emerged from studies on null-mutant mice and autism spectrum disorders (ASD) patients, we set out to examine pathways underlying functions of Cntn6 using a proteomics approach. We identified the cell adhesion GPCR latrophilin-1 (Lphn1, a.k.a. CIRL1/CL, ADGRL1) as a binding partner for Cntn6 forming together a heteromeric cis-complex. Lphn1 expression in cultured neurons caused reduction in neurite outgrowth and increase in apoptosis, which was rescued by coexpression of Cntn6. In cultured neurons derived from Cntn6-/- mice, Lphn1 knockdown reduced apoptosis, suggesting that the observed apoptosis was Lphn1-dependent. In line with these data, the number of apoptotic cells was increased in the cortex of Cntn6-/- mice compared to wild-type littermate controls. These results show that Cntn6 can modulate the activity of Lphn1 by direct binding and suggests that Cntn6 may prevent apoptosis thereby impinging on neurodevelopment.